The use of natural antioxidants (oregano and sage) to reduce hexanal production in precooked chicken during chill storage - MARQUES PINO, Lilian; CAVALEIRO, Carlos; CASTILHO PhD, Maria da Conceição; BISMARA REGITANO D´ARCE PhD, Marisa Aparecida; DA SILVA TORRES, Elizabeth Aparecida; RAMOS, Fernando (Vitae, 2013)
Background: The properties of plants with food preservation potential are well known since the antiquity. In recent years, the use of herbs and spices to improve the sensory characteristics and to extend the shelf-life of foods has been growing. Objectives: To compare oregano (Origanum vulgare L.) and sage (Salvia officinalis L.) as a natural antioxidant in balls of chicken breast and added 0.50% salt. Methods: Samples of chicken meatballs were pre-cooked for 8 minutes in a water bath at 80º C, and packaged in polyethylene bags with three layers, specific for vacuum cooking and high temperatures. The samples were separated into three groups: control (just salt), 0.10% oregano (dry plant) and sage 0.10% (dry plant), stored at -20º C for 144 hours. The tests to verify the formation of hexanal in samples were performed in the period of 0, 48, 96 and 144 hours of refrigerated storage. The determination of hexanal, extracted by micro-extraction (headspace solid phase micro-extraction - HS-SPME), was used as an indicator of the lipid oxidation of the samples. The analysis was conducted by a gas chromatograph coupled with a mass detector (GC-MS). The method was evaluated according to the validation parameters such as linearity, repeatability and detection limit. The extraction was conducted at 70º C using a fiber (DVD / CAR / PDMS) exposed for 20 minutes in the headspace after 5 minutes of equilibrium between the sample and the headspace. Results: Samples added 0.10% oregano or sage had effective protection in the development of hexanal, compared to control samples. The development of hexanal was significantly higher in the control samples, 34 μg of hexanal/100 g of sample at the beginning and 280 µg/100 g sample at the end of refrigerated storage. Conclusion: Herbs were effective in controlling the development of hexanal. However, the oregano was more effective than sage in preventing the formation of hexanal in chicken meatballs pre-cooked. The level of hexanal in herbs at the end of the storage period was 5 μg hexanal/100 g sample for oregano and 23 µg hexanal/100 g sample for sage.